Valuation of companies through the methos of discount of flow of funds - Vilca Maldonado, Maritza Pilar (2018)
Objective: to describe the types of valuation used by mining companies. Method: the free cash flow method known as weighted average cost of capital will be used, since it is the method that is most suitable for the valuation of companies that operate continuously. Result: Based on this method, many companies have been considered as fund generators, and valued as financial assets that have a present value. Conclusions: when incorporating both financial and business risk, this method will allow you anticipate money balances.